Fresh frozen plasma transfusion in the neonatal population: A systematic review. (September 2022) - Sokou, Rozeta; Parastatidou, Stavroula; Konstantinidi, Aikaterini; Tsantes, Andreas G.; Iacovidou, Nicoletta; Doxani, Chrysoula; Piovani, Daniele; Bonovas, Stefanos; Stefanidis, Ioannis; Zintzaras, Elias; Tsantes, Argirios E.
Abstract: Although fresh frozen plasma (FFP) transfusions are common practice in neonatology, robust evidence on their use is lacking. The aim of this study was to systematically review the literature for data on the practice of FFP transfusions in neonates and their association with neonatal morbidity and mortality. The authors identified 40 studies, which met the inclusion criteria for this review. It was demonstrated that the practice of FFP transfusions significantly varies throughout the world. The majority of FFP transfusions are administered "prophylactically", without evidence of active bleeding. Although FFP transfusions may restore coagulation tests results, they do not alter the clinical outcome of the neonates. Reactions following transfusions are probably underestimated in neonates, often undiagnosed and thus, underreported. High quality RCTs aiming to evaluate the effectiveness of FFP in specific clinical conditions are urgently needed, as they could change long-standing FFP transfusion practices, and help reduce neonatal morbidity and mortality.